Surgical management of a large peritoneal pseudocyst causing acute kidney injury secondary to abdominal compartment syndrome in a rare case of congenital absence of omentum during pregnancy. (September 2016) - Jones, Benjamin P; Hunjan, Tia; Terry, Jayne
Complete congenital absence of the omentum is very rare with only one previously reported case. We present a unique case of the management of a pregnant woman with a large pelvic pseudocyst caused by complications related to congenital absence of omentum, resulting in acute kidney injury, likely secondary to acute compartment syndrome. This case highlights the importance of considering acute compartment syndrome in critically unwell pregnant women and reiterates the need to measure intra-abdominal pressure when clinically indicated. Given that pregnancy is in itself a state of intra-abdominal hypertension, obstetricians should maintain a high index of suspicion in the context of additional risk factors.